Exploring More on Dictyosporiaceae: The Species Geographical Distribution and Intriguing Novel Additions from Plant Litter - Danushka S. Tennakoon; Nimali I. de Silva; Sajeewa S. N. Maharachchikumbura; Darbhe J. Bhat; Jaturong Kumla; Nakarin Suwannarach; Saisamorn Lumyong (Diversity, 2023)
Five fungal taxa collected from plant litter in Chiang Mai province, Thailand, are described with illustrations. The maximum likelihood, maximum parsimony, and Bayesian analyses of combined loci of the internal transcribed spacer (ITS), large subunit nuclear ribosomal DNA (LSU), and translation extension factor 1-α (tef1-α) region were used for phylogeny analyses. Dictyocheirospora acaciae is introduced as a new species from Acacia dealbata. Based on size differences in conidiomata, conidia, and DNA sequence data, it is separated from the other species in the genus. Four new host records, Dictyocheirospora garethjonesii, Di. taiwanense, Dictyosporium digitatum, and Pseudocoleophoma zingiberacearum are also reported from Bismarkia nobilis, Ficus benjamina, Cyperus aggregatus, and Hedychium spicatum, respectively. Detailed descriptions, microphotographs, and phylogenetic information were provided, and all the species were compared to similar taxa. It is noted that there is still a necessity for a collective worldwide account of the distribution of Dictyosporiaceae species. Therefore, we compiled the geographical distributions and host species associations of all the so far known Dictyosporiaceae species and discussed them here.